2011
DOI: 10.1055/s-0030-1271136
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich der Bildqualität zweier unterschiedlicher mobiler 3-dimensionaler Röntgen-C-Bögen mit einem konventionellen CT bei der Darstellung relevanter Strukturen am knöchernen Becken

Abstract: When using intraoperative 3D imaging with the cone beam CT technique for pelvic injury, image acquisition in low-dose mode is adequate in terms of signal-to-noise ratio and image quality. The image quality does not correlate linearly with a higher radiation dosage. Therefore, the pelvic trauma surgeon using this technique is encouraged to gather his own experience with low dose modes thereby reducing patient radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The image quality of mobile 3D devices is limited, in comparison to conventional CT scanners [28, 29]. Nevertheless, an evaluation of the bone morphology and implant position is possible [28, 30].…”
Section: Discussionmentioning
confidence: 99%
“…The image quality of mobile 3D devices is limited, in comparison to conventional CT scanners [28, 29]. Nevertheless, an evaluation of the bone morphology and implant position is possible [28, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Often, these 3D scans are considered equal to CT scans regarding the parameters reduction and implant placement. Standardized technical evaluation of possible image quality of intraoperative and image quality in anatomical regions without implants has been described in several publications [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our institution has the distinctive availability of several intraoperative imaging systems from which to select, including a multidetector CT (MDCT) scanner (CT A); two mobile CT units (CT B and CT C); a C-arm (D); and fluoroscopy (E). Although a number of studies have reported the radiation exposure of some of the modalities, 4 , 5 and just recently, Hecht et al 6 published the accuracy of instrumentation using CT B, we are unaware of any literature examining the radiation exposure of MDCT A or CT B. In addition, we are unaware of any study that has directly compared all these modalities with respect to commonly performed spinal surgery.…”
mentioning
confidence: 99%